2020
DOI: 10.1017/ssh.2020.13
|View full text |Cite
|
Sign up to set email alerts
|

Drafting the Dutch: Selection Biases in Dutch Conscript Records in the Second Half of the Nineteenth Century

Abstract: Conscription records are considered to be the best sources for studying heights over cohorts. This article discusses the various steps and selection mechanisms involved in the conscription system of the Netherlands, which was more or less similar to the systems found in other European countries. Starting with a birth cohort of 4,436 boys, we run a series of regressions on the likelihood to be registered at all and to have one’s height recorded. We discuss the effects of cohort attrition through mortality and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…As seen in other studies on the evolution of adult height, the main indicator of biological living standards [ 8 , 10 , 68 , 69 , 70 ], the SB data show a close relationship with the economic cycles of the island. At the end of the 19th century, the insular advantage was probably due to the improvements in foreign trade driven by the establishment of free trade.…”
Section: Discussionsupporting
confidence: 82%
“…As seen in other studies on the evolution of adult height, the main indicator of biological living standards [ 8 , 10 , 68 , 69 , 70 ], the SB data show a close relationship with the economic cycles of the island. At the end of the 19th century, the insular advantage was probably due to the improvements in foreign trade driven by the establishment of free trade.…”
Section: Discussionsupporting
confidence: 82%
“…In principle, they would be enlisted when they failed to show up. In other research, it has been shown that boys from elite groups managed to avoid the examination altogether (Quanjer & Kok, 2020). Finally, after about 1900, boys who were to be exempted because a brother had been enlisted were no longer measured.…”
Section: Setting and Sourcesmentioning
confidence: 99%
“…Society in Indonesia at that time was divided into three groups. The highest stratum is the European group which contains the Dutch (Quanjer & Kok, 2020). The second strata is filled with the Foreign Eastern group which contains Arab and Chinese descent (Mark Horton, Boivin, & Crowther, 2021).…”
Section: Racism In Indonesia and The Bible Agementioning
confidence: 99%